Innovative Approaches to Managing the Development of Industrial Enterprises - Olimjanovich, Dusmatov Begmuhammad; O’g’li, Fozilov Vakhobjon Akrom (Research Parks Publishers, 2023)
The effectiveness of innovation activity in an enterprise depends on many factors. The main of them are the degree of involvement of employees of industrial enterprises in this process, making innovation activities at industrial enterprises organized and purposeful, the level of incentives to search for innovations and their implementation.